2014
DOI: 10.15386/cjmed-303
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal bacterial overgrowth is associated with intestinal inflammation in the irritable bowel syndrome

Abstract: Background and aimSmall intestinal bacterial overgrowth is encountered in bowel disorders, including irritable bowel symptoms. Low degrees of inflammation have been recently reported in the irritable bowel syndrome. We looked for the association between intestinal inflammation and small intestinal bacterial overgrowth in irritable bowel syndrome.MethodsSmall intestinal bacterial overgrowth was assessed by the H2 glucose breath test in 90 consecutive patients with irritable bowel syndrome. A check-up of the ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…76 A recent meta-analysis showed that the incidence of SIBO in IBS patients is 36.7% (95% CI, 24.2-44.6) and it was closely associated with intestinal inflammation. 77 , 78 There are few studies focusing on the relationship between SIBO and FD. In a small sample Brazilian study, SIBO was found in 56.5% (13/23) of patients with FD but not observed in healthy controls ( P = 0.005).…”
Section: The Role Of Non-infectious Inflammation In the Pathogenesis Of Irritable Bowel Syndrome Functional Dyspepsia And Overlap Syndrommentioning
confidence: 99%
“…76 A recent meta-analysis showed that the incidence of SIBO in IBS patients is 36.7% (95% CI, 24.2-44.6) and it was closely associated with intestinal inflammation. 77 , 78 There are few studies focusing on the relationship between SIBO and FD. In a small sample Brazilian study, SIBO was found in 56.5% (13/23) of patients with FD but not observed in healthy controls ( P = 0.005).…”
Section: The Role Of Non-infectious Inflammation In the Pathogenesis Of Irritable Bowel Syndrome Functional Dyspepsia And Overlap Syndrommentioning
confidence: 99%
“…showed that the prevalence of SIBO in patients with IBS varies between 39% and 54%. However, these meta‐analyses were published about a decade ago, and there has been a substantial influx of good quality studies using glucose hydrogen breath test (GHBT), and lactulose hydrogen breath test (LHBT) . Also, the earlier meta‐analysis focused on breath tests only, which are non‐invasive alternatives, albeit inferior to the gold standard method of quantitative upper gut aspirate culture.…”
Section: Introductionmentioning
confidence: 99%
“…Raia et al studied the concentration of FC in 30 pediatric patients with cystic fibrosis; FC levels were reported to be significantly higher compared to controls (P<0.01) and significantly lower compared to 15 patients with IBD (P<0.001) [38]. Further studies have linked higher levels of FC to small intestinal bacterial overgrowth [39], food allergy, gastroesophageal reflux disease [40], hepatic encephalopathy in patients with liver cirrhosis [41], and iatrogenic causes, such as gastric bypass surgery [42].…”
Section: Role Of Fc In Other Gi Diseasesmentioning
confidence: 99%